2008
DOI: 10.2499/9780896291690rr160
|View full text |Cite
|
Sign up to set email alerts
|

The bang for the birr: Public expenditures and rural welfare in Ethiopia

Abstract: , the Discussion Paper series within each division and the Director General's Office of IFPRI were merged into one IFPRI-wide Discussion Paper series. The new series begins with number 00689, reflecting the prior publication of 688 discussion papers within the dispersed series. The earlier series are available on IFPRI's website at www.ifpri.org/pubs/otherpubs.htm#dp. 2 IFPRI Discussion Papers contain preliminary material and research results. They have not been subject to formal external reviews managed by IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In other words, these different types of public expenditure variously contribute to poverty reduction, economic growth, and enhancing rural welfare. For example, empirical evidence by Mogues et al 2008 indicates that the public investment in road infrastructure has relatively higher return than investment in agriculture, health and education in Ethiopia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, these different types of public expenditure variously contribute to poverty reduction, economic growth, and enhancing rural welfare. For example, empirical evidence by Mogues et al 2008 indicates that the public investment in road infrastructure has relatively higher return than investment in agriculture, health and education in Ethiopia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors argue that rural investments are more important for poverty reduction than for growth. Biru, Zeller, and Loos (2018) find that government‐supported agricultural programmes do have substantial success in reducing poverty, but Mogues (2011) claims that APS does not increase rural welfare in Ethiopia.…”
Section: Previous Researchmentioning
confidence: 99%
“…Fan and Zhang (2008) and Tijani, Oluwasola, and Baruwa (2016) studied public expenditure in support of agriculture and rural development, and observed significant and positive effects on growth and welfare. Likewise, using district‐ and regional‐level public expenditure data and household‐level production data and analysing the cases of Malawi, Ethiopia and Ghana, respectively, Benin, Thurlow, Diao, McCool, and Simtowe (2008), Mogues (2011) and Benin, Mogues, Cudjoe, and Randriamamonjy (2009) found that the provision of various public goods and services in agriculture and allied sectors (education, health and rural roads) have substantial impact on agricultural productivity and rural welfare.…”
Section: Public Expenditure Agricultural Performance and Poverty Reduction Nexusmentioning
confidence: 99%
“…This calls for a robust analysis of the welfare and food security implications of the strategic objectives and the accompanying investment areas such that governments can properly gear their scarce resources towards those investment options that can bring about greater returns. However, so far, relatively few studies have provided guidance for public resource allocation across competing agricultural investment options in the African context (Mogues, 2011; Pauw & Thurlow, 2014; Benfica et al, 2019).…”
Section: Introductionmentioning
confidence: 99%